The role of mutual in-feeding in maintaining problematic self-narratives: exploring one path to therapeutic failure - Gonçalves, Miguel M. (2011)
According to the author’s narrative model of change, clients may maintain a problematic self-stability across therapy, leading to therapeutic failure, by a mutual in-feeding process, which involves a cyclical movement between two opposing parts of the self. During innovative moments (IMs) in the therapy dialogue, clients’ dominant self-narrative is interrupted by exceptions to that self-narrative, but subsequently the dominant self-narrative returns. The authors identified return-to-the-problem markers (RPMs), which are empirical indicators of the mutual in-feeding process, in passages containing IMs in 10 cases of narrative therapy (five good-outcome cases and five poor-outcome cases) with females who were victims of intimate violence. The poor-outcome group had a significantly higher percentage of IMs with RPMs than the good-outcome group. The results suggest that therapeutic failures may reflect a systematic return to a dominant self-narrative after the emergence of novelties (IMs)